2008
DOI: 10.1001/archsurg.2007.39
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Hepatocellular Carcinoma Following Liver Transplantation

Abstract: Liver transplantation is a viable treatment option for select patients with HCC and end-stage liver disease. However, in approximately 20% of patients, recurrent HCC is the rate-limiting factor for long-term survival. Despite identification of clinical parameters that may stratify patients at high risk and exhaustive preoperative staging, cancer recurrence is likely the result of microscopic extrahepatic disease. With a desperate donor organ shortage, locoregional ablation techniques and resection are being em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(88 citation statements)
references
References 73 publications
(82 reference statements)
1
82
1
1
Order By: Relevance
“…With liver transplantation development in recent years, the 5-year survival rate is significantly improved [2]. However, recurrence and metastasis of HCC after LT remains a formidable problem; several large centers have reported that the recurrence rate was approximately 20%, which is the rate-limiting factor for long-term survival [3]. So currently, prevention and treatment of tumor recurrence is one of the hot issues for the research for HCC patients after liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…With liver transplantation development in recent years, the 5-year survival rate is significantly improved [2]. However, recurrence and metastasis of HCC after LT remains a formidable problem; several large centers have reported that the recurrence rate was approximately 20%, which is the rate-limiting factor for long-term survival [3]. So currently, prevention and treatment of tumor recurrence is one of the hot issues for the research for HCC patients after liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Although a variety of studies have demonstrated that the 5-year survival for HCC patients after liver transplantation is approximately 70%, tumor recurrence after transplantation is the rate-limiting factor to achieving long-term survival. The actual incidence of HCC recurrence after transplantation has been reported to vary from 6.4 to 56.5%; survival is significantly lower in patients with recurrence (Zimmerman et al 2008). Several clinicopathological variables such as vascular invasion, lymph node metastasis, tumor size larger than 5 cm, bilobar involvement, and multiple tumor nodules have been identified as important prognostic factors for both tumor recurrence and survival.…”
Section: Introductionmentioning
confidence: 99%
“…A recurrent HCC should be considered a metastasis of the original tumor reflecting a systemic dissemination of the tumor; those patients may benefit from all surgical, medical or radiological treatments for the HCC, as in the pre-transplant setting, but re-transplantation is contraindicated and the prognosis is really poor, with about 22% chance of survival at 5 years, with a median of less than one year after diagnosis [3,10,11]. Conversely, the development of a de novo HCC can allow even re-transplantation, such was the case in our first patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of HCC usually develops early after LT and is strictly dependent on tumor grading and presence of microvascular invasion [2,3]. In addition, LT recipients are exposed to a higher risk of developing other de novo malignancies as a consequence…”
Section: Introductionmentioning
confidence: 99%